Implementasi Media Pembelajaran Berbasis Teknologi Animasi dan Simulasi Interaktif Pada Pembelajaran IPAS - Mina Listiana; Mike Herlinawati; Muhammad Rifki Supyadi (Universitas Muhammadiyah Kuningan, 2024)
This research aims to describe the effectiveness of science and science learning using learning media based on animation technology and interactive simulations. The method used in this research is descriptive qualitative where the instruments used are observation, interviews and documentation. The results of this research are that the use of learning media, especially technology-based media, is able to create more effective learning and students become more motivated in participating in learning. Based on these results, it can be concluded that the use of technology-based media can increase the effectiveness of learning and it is hoped that all education in Indonesia will be able to take advantage of changes or developments in this technology for education. Keywords: Effectiveness of Science and Technology Learning, Animation and Interactive Media, Technology Based Learning.